Effects of technology in nursing care - Karina Jazmin Marrujo Pérez; Domingo Palacios-Ceña (Universidad de Alicante, 2017)
The vision of technology as an aid to improve the conditions of those influences multiple aspects of health and care. Technology in nursing and care covered; the role of the nurse as a link between technology and the patient, the application of an ethic of care, training of management of technology and education in various fields. Lack of management with performance problems can cause anxiety and stress on nurses, the use of technology within the training of nurses, reinforces the skills with which it comes to clinical practice or institutions, promoting adaptation to the workplace. The innovate depends not only on health institutions, implementation of new technologies, seeks that professionals see an opportunity for professional growth and is interested in the development of projects that are aimed to use and implementation. The technology is a neutral element, are the actions of the nurse which determine the presence of positive or negative associated with the application of technology aspect